A new discoid stele in Sepúlveda (Segovia). About a recension to ERSG - Santos Yanguas, Juan; Hoces de la Guardia Bermejo, Ángel Luis (Gerión. Revista de Historia Antigua, 2012)
In this article we answer to a recession ERSg published in 2005, in which Dr. D. Manuel Ramírez Sánchez made known epigraphic piece in the square in front of the church of Virgen de la Peña, which we could not see, then, between inspection and ours, there was remodeling the pavement, so that the piece was hidden. Moreover, comparing the piece in the photos could prove is not Roman, as shown in our reviews.